A Qualitative Investigation of Music Use among Amateur and Semi-Professional Golfers - Nicole T. Gabana; Jasmin Hutchinson; James Beauchemin; Matthew Powless; Julia Cawthra; Aaron Halterman; Jesse Steinfeldt (MDPI AG, 2019)
Music use in golf receives minimal attention from both applied and empirical perspectives. Golfers, coaches, and sport psychology practitioners alike may benefit from understanding and utilizing music within their work. Since music use in golf has become an increasingly common practice, the purpose of the current study was to investigate current music use among golfers using a qualitative approach. Researchers aimed to identify potential psychological and physiological effects derived from music use during golf practice and pre-performance, given the limited empirical research in this area to date. Semi-structured interviews were conducted with ten amateur and semi-professional golfers (five male, five female, Mage = 22.9 years, SD = 5.04 years). Consensual qualitative research (CQR) methodology was used to analyze the interview data. Six domains emerged from the CQR analysis regarding participants’ self-reported music use in golf: tempo, attention, physiological regulation, psychological regulation, effects of music on performance perceptions, and context (to use or not to use). Given the capacity of carefully selected music to elicit profound affective, neurophysiological, and behavioral responses, there is clear potential for mental performance consultants to utilize music in working with golfers in training contexts. Implications, caveats, and future research recommendations are provided.